Infant development and parents’ perceptions associated with use of the harris infant neuromotor test - Maria Vera Lúcia Moreira Leitão Cardoso; Polyana Candeia Maia; Larissa Paiva Silva; Grazielle Roberta Freitas da Silva; Virginia Ellen Hayes; Susan Richardson Harris (Rev Rene)
This work aimed to identify the socio-economic, health, and educational profiles of parents, as well as their perceptions of their infants’ motor development in the first year of life. This descriptive study was carried out from November/2008 to February/2009. Participants in the study were 50 infants and 50 parents/guardians, in Fortaleza-Brazil. We used the Portuguese version of the Harris Infant Neuromotor Test (HINT) with infants ranging in age from 3 months to 11 months and 20 days. Twenty-six infants (52%) were boys. The mean age of the mothers was 24.5 years. Of the caregivers, 23 (46%) lived in stablemarital relationships, Sixteen (32%) had finished secondary education, and 27 (54%) of the families had incomes between R$ 464,72 (US$202.05) and R$ 929,44 (US$404.10). Participating caregivers were generally accurate in their own perceptions of their children’s development when compared to the numeric HINT scores assessed by nurses trained in infant development.